Revisiting the Case of Sarah Newbury's Death from Mollities Ossium. (3rd July 2022) - Mulligan, Michael; Bonar, Fiona; Fanburg-Smith, Julie; Melhem, Lina; Messiou, Christina; Kocoglu, Mehmet; Streeten, Elizabeth
Abstract: Multiple myeloma and its precursor and variant types represent some of the most common hematologic malignancies in adults. These plasma cell dyscrasias are well-known in modern medicine. There are well-established clinical, laboratory, and pathologic criteria for diagnosis and staging. There is debate about the diagnosis of some of the earliest cases of myeloma described in the literature. We present a critical review of one such case.